2017
DOI: 10.1515/ejthr-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

A study of domestic honeymoon tourism in Turkey

Abstract: Abstract:Honeymoon tourism is an important research area in tourism and travel literature because of its increasing economic importance for host destinations and their specific niche market characteristics. This study used a survey to investigate demographics, the importance of attributes in destination selection, overall satisfaction, loyalty and souvenir purchase preference amongst 540 domestic honeymoon tourists visiting Antalya, Turkey. It also identified in the context of destination marketing both domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 29 publications
2
21
1
Order By: Relevance
“…Meanwhile, European countries and most developed societies, such as Germany and Italy, have realized the substantial positive impacts of tourism at a much earlier time and have been benefiting from this industry for many years (Balaguer and Cantavella-Jorda, 2002;Dritsakis, 2004). Some developing countries, such as Taiwan, Malaysia and Turkey, have also invested fundamentally in tourism and hospitality infrastructures and have subsequently generated a remarkable amount of tourism and hospitality revenues to compensate for their lack of income from their under-earth resources (Kim and Chen, 2006;Musa, 2000;Ünal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, European countries and most developed societies, such as Germany and Italy, have realized the substantial positive impacts of tourism at a much earlier time and have been benefiting from this industry for many years (Balaguer and Cantavella-Jorda, 2002;Dritsakis, 2004). Some developing countries, such as Taiwan, Malaysia and Turkey, have also invested fundamentally in tourism and hospitality infrastructures and have subsequently generated a remarkable amount of tourism and hospitality revenues to compensate for their lack of income from their under-earth resources (Kim and Chen, 2006;Musa, 2000;Ünal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al, 2020;Ünal et al, 2017). Additionally, emotions (Bulcroft et al, 2000;Lin, 2014), memorable experiences and memories (Bulcroft et al, 2000;Ünal et al, 2017), and behavioral intention (Ünal et al, 2017) have been noted as key constructs underlying the HTE. For instance, when examining the social narratives of honeymoons in American history , Bulcroff et al (1997) identified newlyweds' emotional experiences as a recurring theme.…”
Section: Key Constructs Underpinning the Htementioning
confidence: 99%
“…Three destinations (i.e., Chiang Mai, Pattaya, and Phuket Island) were chosen, representing those most frequently visited by Chinese honeymooners (F. Wang et al, 2015). In line with the operationalization of honeymooners in prior work (Ünal et al, 2017;Winchester et al, 2011), honeymooners were defined in this study as newlywed couples taking a holiday immediately or shortly after their marriage ceremony or marital registry. Field interviewers identified (by judging their spoken language and asking where they came from) and approached potential qualified respondents in public areas (airports, shopping centers, resort hotel lobbies, and recreational activity sites).…”
Section: Qualitative Phasementioning
confidence: 99%
See 2 more Smart Citations